الدور التعليمي للقناة الفضائية التربوية السورية في تنمية أداء تلاميذ الحلقة الأولى من التعليم الأساسي من وجهة نظر الموجهين التربويين (دراسة ميدانية في مدينة اللاذقية) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدفت هذه الدراسة إلى معرفة وجهات نظر الموجهين التربويين في مدينة اللاذقية حول الدور التعليمي للقناة الفضائية التربوية السورية في تنمية أداء تلاميذ الحلقة الأولى من التعليم الأساسي وقد تمت هذه الدراسة على عينة من الموجهين التربويين في مديرية تربية اللاذقية للعام الدراسي 2012-2013 وبلغت العينة (52) موجهاً وموجهة واستخدم الباحث في دراسته استبانة مؤلفة من (16) عبارة واعتمد المنهج الوصفي التحليلي , وتوصلت  الدراسة إلى النتائج التالية: _  لا توجد فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.05) بين متوسط إجابات الموجهين التربويين فيما يتعلق بالدور التعليمي للقناة الفضائية التربوية السورية في تنمية أداء تلاميذ الحلقة الأولى من التعليم الأساسي وفقاً لمتغير الجنس. _  وجود فروق ذات دلالة إحصائية، عند مستوى الدلالة (0.05) بين متوسط إجابات الموجهين التربويين فيما يتعلق بالدور التعليمي للقناة الفضائية التربوية السورية في تنمية أداء تلاميذ الحلقة الأولى من التعليم الأساسي وفقاً لمتغير التخصص. وقد قدم الباحث المقترحات التالية: - الدعوة إلى التنسيق المستمر بين قطاع التربية وقطاع الإعلام بهدف التركيز على المحتوى التربوي الذي يقدم للمتعلمين من خلال البرامج التعليمية . -وضع مقترحات لتطوير المحتوى التعليمي الإعلامي وفقاً للدور التعليمي للقناة الفضائية التربوية السورية. This research  aims to define the teaching role of the Syrian Educational Satellite  Channel in developing the performance of the students of the first phase of basic education,  according to a sample of educational supervisors in Lattakia. The sample of the study included (52) supervisors in Lattakia. The researcher adopted the descriptive analytic method, and used as a tool a questionnaire of 16 items, The research results: 1-There are no statistically significant differences at the indication level (0.05) among the average answers of supervisors as to the educational role of the Syrian Satellite Channel regarding the gender variable. 2- There are statistically significant differences at the indication level (0.05) among the average answers of supervisors as to the educational role of the Syrian Satellite Channel regarding the specialization variable. The researcher recommended the following: - calling for constant coordination between the media and the educational sector in order to focus on educational content offered to the learners through educational programs. - presenting suggestions to develop media content and educational content according to the educational role of the Syrian Educational Satellite Channel.